Are Individual Differences in Response to Intervention Influenced by the Methods and Measures Used to Define Response? Implications for Identifying Children With Learning Disabilities. (November 2020) - Hendricks, Emma L.; Fuchs, Douglas
Response to intervention (RTI) has been promoted for nearly 20 years as a valid supplement to or alternative method of learning disability (LD) identification. Nevertheless, important unresolved questions remain about its role in disability identification. We had two purposes when conducting this study of 229 economically and racially diverse poor readers in Grades 4 and 5 in 28 public elementary and middle schools in Nashville. First, we examined predictors of the children's response to a reading comprehension tutoring program. Second, we explored the utility of different methods (growth vs final status) and measures (near- and mid-transfer vs far-transfer) in operationalizing "response, " and whether these contrasting methods and measures identified similar children. Findings indicated students with higher pretreatment scores on expressive vocabulary, nonverbal IQ, teacher ratings of attention, and reading comprehension measures were more likely classified as responsive with final status methods. Students with lower pretreatment comprehension scores were more likely identified as responsive with growth methods. These and other findings suggest "response" is strongly context dependent, raising questions about the validity of RTI as a means of disability identification.